Edukasi Ilmu Tajwid Dalam Meningkatkan Kemampuan Membaca Al-Quran Santri Pondok Pesantren Hidayatul Mustaqim Bulusari Tarokan Kediri - Muh. Fatihuddin; Abd. Majid Abror (LP3M IAIFA Kediri, 2020)
Understanding tajwid science is one of the components for Santri in reading the Quran. Understand the laws of reading in the science of tajwid, such as the law of reading nun breadfruit and tanwin, the law of mim breadfruit, mad law and the nature of letters which is creteria in reading the Quran. Tajwid science is the science of how to read the Qur'an precisely, namely by making a letter sound from its origin (makhraj), in accordance with the character of the sound (sifat) and the consequences of the nature of the letter, knowing where to stop (waqaf) and where to start reading again (ibtida'). The law of studying tajwid science is fardu kifayah, but applying tajwid science to the recitation of the Qur'an the law becomes fardu 'ain for male Muslims and women. In observations conducted in Madrasah Diniyah Wustho Hidayatul Mustaqim Dusun Bulusari Village Bulusari District Tarokan Kediri Regency, the author found some problems including about the understanding of tajwid science some low Santri and lack of practice of reading the Quran that affects the ability to read the Quran Santri. Based on this, the author conducted research on Santri class IX Madrasah Diniyah Wustho Hidayatul Mustaqim which is located in the pondok Pesantren Hidayatul Mustaqim Foundation with the aim to improve Santri's ability to read the Quran by learning tajwid science.